Physical Exercise Behaviors and Depressive Symptoms Among Elderly Chinese Women: Focus on Exercise Components - Cui Y; Huang C; Gong Q; Guo F; Li W; Zhang L; Cai X; Wang Y (Dove Medical Press, 2021)
Yufei Cui,1,2 Cong Huang,3 Qiang Gong,2 Feng Guo,1 Wang Li,1 Luyao Zhang,1 Xianfeng Cai,1 Yongxiang Wang1 1Institute of Exercise Epidemiology and Department of Physical Education, Huaiyin Institute of Technology, Huaian, Jiangsu Province, People’s Republic of China; 2Department of Medicine and Science in Sports and Exercise, Tohoku University Graduate School of Medicine, Sendai, Japan; 3Department of Sports and Exercise Science, College of Education, Zhejiang University, Hangzhou, Zhejiang Province, People’s Republic of ChinaCorrespondence: Yufei CuiInstitute of Exercise Epidemiology and Department of Physical Education, Huaiyin Institute of Technology, Huaian, 223003, Jiangsu Province, People’s Republic of ChinaEmail bigshowgod@yahoo.co.jpCong HuangDepartment of Sports and Exercise Science, College of Education, Zhejiang University, 148 Tianmushan Road, Hangzhou, 310007, People’s Republic of ChinaEmail cohuang@zju.edu.cnPurpose: Several studies have investigated the association between physical exercise and depressive symptoms in the elderly population. However, the relationship between components of physical exercise such as frequency, intensity, duration, and depressive symptoms remains unclear. This study was conducted on elderly Chinese women to investigate the association between each component of physical exercise and depressive symptoms and to examine the association between physical exercise patterns and depressive symptoms.Patients and Methods: A total of 1429 Chinese women aged ≥ 60 years were enrolled in this cross-sectional study and provided information on their exercise behaviors through a self-reported questionnaire. Depressive symptoms were assessed using the Zung Self-Rating Depression Scale. Multiple logistic regression analysis was used to estimate adjusted odds ratios (ORs) to measure the association between exercise behaviors and depression.Results: High frequency, moderate intensity, long duration, and exercise habits were significantly associated with lower levels of depressive symptoms. Furthermore, participants with more than one optimal exercise behavior were more likely to have a lower risk of depressive symptoms. These associations were not changed after adjustment for confounding factors.Conclusion: This study shows that exercise behaviors were significantly associated with the risk of developing depression. This finding suggests that keeping an optimal exercise behavior may be associated with a lower risk of depressive symptoms in elderly Chinese women.Keywords: physical exercise, depressive symptoms, elderly women, cross-sectional study